2021
DOI: 10.1126/sciadv.abg2697
|View full text |Cite
|
Sign up to set email alerts
|

ERK signaling mediates resistance to immunomodulatory drugs in the bone marrow microenvironment

Abstract: Immunomodulatory drugs (IMiDs) have markedly improved patient outcome in multiple myeloma (MM); however, resistance to IMiDs commonly underlies relapse of disease. Here, we identify that tumor necrosis factor (TNF) receptor-associated factor 2 (TRAF2) knockdown (KD)/knockout (KO) in MM cells mediates IMiD resistance via activation of noncanonical nuclear factor κB (NF-κB) and extracellular signal–regulated kinase (ERK) signaling. Within MM bone marrow (BM) stromal cell supernatants, TNF-α induces proteasomal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Hence, we propose that in preclinical studies, monitoring the impact of potential drug candidates on the proliferation and fibroblastic differentiation of BM mesenchymal cells in co-culture with MM cells, as described in our model, is vital to determine more accurately possible drug efficacy against MM. For example, BM-mediated resistance to pomalidomide involves the activation of ERK signalling, as determined by changes in the proliferation of MM cells grown in co-culture with primary BM stromal cells or their conditioned media [51]. Similarly to previous reports where they use MM cell proliferation as a single readout for drug efficacy, our current results also predict that ERK inhibitors could inhibit resistance to dexamethasone.…”
Section: Discussionsupporting
confidence: 79%
“…Hence, we propose that in preclinical studies, monitoring the impact of potential drug candidates on the proliferation and fibroblastic differentiation of BM mesenchymal cells in co-culture with MM cells, as described in our model, is vital to determine more accurately possible drug efficacy against MM. For example, BM-mediated resistance to pomalidomide involves the activation of ERK signalling, as determined by changes in the proliferation of MM cells grown in co-culture with primary BM stromal cells or their conditioned media [51]. Similarly to previous reports where they use MM cell proliferation as a single readout for drug efficacy, our current results also predict that ERK inhibitors could inhibit resistance to dexamethasone.…”
Section: Discussionsupporting
confidence: 79%
“…TRAF2-deficient multiple myeloma cells enhance immunomodulatory drug resistance through activation of non-canonical NF-κB signaling and ERK signaling. 522 Low MHC-I expression may lead to resistance to immune checkpoint inhibitors by inhibiting the IFN-γ signaling pathway, whereas guanine nucleotide-binding protein subunit gamma 4 (GNG4) maintains MHC-I expression through the NF-κB signaling. 523 Inhibitors of the deubiquitinating enzyme ubiquitin-specific proteases (USP) 8 activate NF-κB signaling to trigger innate immune responses and MHC-I expression, thereby remodeling the inflammatory tumor microenvironment and enhancing the antitumor efficacy of anti-PD-1/PD-L1 therapies.…”
Section: Strategies For Targeting Nf-κb Signaling In Human Diseasesmentioning
confidence: 99%
“… 127 Using this candidate discovery to their advantage, the authors showed that pretreatment of MM cells with proteasome inhibitors or NEDD8-activating enzyme inhibitors eliminates the impact of the constitutive photomorphogenesis 9 signalosome complex on CRBN, thereby increasing the effectiveness of IMiD therapy. Likewise, several alternative therapeutic strategies have been discovered including the cardioprotective drug dexrazoxane that inhibits DNA topoisomerase IIβ 130 and MEK inhibitors, 131 which have been observed to overcome IMiD resistance in MM and improve patient survival.…”
Section: Crispr Screens In MMmentioning
confidence: 99%